Efektivitas Penggunaan E-Modul Pada Mata Kuliah Statistika Di Program Studi Pendidikan Teknik Bangunan Fakultas Teknik Universitas Negeri Jakarta - Naufal Dzakwan; R. Eka Murtinugraha; Riyan Arthur (Risenologi, 2021)
This research aims to find out the effectiveness of the use of e-modules in statistics courses in the Building Engineering Education Study Program of The State University of Jakarta which is seen through learning outcomes. The method used is Quasi Experimental with the form The Randomized Control Group Design. The sample in this study is an affordable sample, namely students who take statistics courses in the 114th semester of 2020/2021. In this study, the sample was divided into two, namely the group given treatment in the form of learning using the teaching materials e-module statistics as an experimental class and the other group using conventional teaching materials as a control class. Data collection is carried out using test instruments of learning outcomes that will be given in experimental classes and control classes. The results showed that the average learning outcome score for the experimental class was 68.79 and for the control class the average score was 55.47. In the test t using the independent sample test technique, the results of  = 4,354    = 1,999. The analysis also showed a significant (2-tailed) rate of 0.000 < 0.05. Based on these results, it can be concluded that the e-module statistics effectively has a positive impact on the learning outcomes of students of the Building Engineering Education Study Program of The State University of Jakarta.